Textile Product Innovative Design: The Practical Exploration of Integrating Fashion with Sustainable Development - Guoxing Chen (Art and Society, 2024)
The textile industry is facing environmental and competitive challenges, urgently requiring innovative transformation. This study deeply analyzes the trends of fashion and sustainable development, exploring the innovative strategies and practical paths of their integration through research and case analysis. The study finds that trends in the fashion industry regarding color, style, and material are influenced by sustainable concepts, and the application of environmental protection materials and the practice of circular economy are gradually becoming mainstream. The demand for integrated products by consumers is increasing, and the potential of emerging markets is huge. Innovative strategies are proposed for material selection, design process, production process, and the application of digital tools, and practical challenges and solutions are discussed. The research enriches the theoretical system, provides a basis for enterprise decision-making, and helps the industry to achieve sustainable development. In the future, technological innovation, consumer demand, industry collaboration, and policies and regulations will jointly promote the industry to a new height.